1997
DOI: 10.1074/jbc.272.8.5208
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear ADP-ribosylation Factor (ARF)- and Oleate-dependent Phospholipase D (PLD) in Rat Liver Cells

Abstract: Two forms of phospholipase D (PLD) have been found to be present in nuclei isolated from rat hepatocytes by measuring phosphatidylbutanol produced from exogenous radiolabeled phosphatidylcholine in the presence of butanol. In nuclear lysates from either rat liver or ascites hepatoma AH 7974 cells, the PLD activity was markedly stimulated by a recombinant ADP-ribosylation factor (rARF) in the presence of the guanosine 5-O-(3-thiotriphosphate) (GTP␥S) and phosphatidylinositol 4,5-bisphosphate. ATP and phorbol-12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 48 publications
(52 reference statements)
1
28
0
1
Order By: Relevance
“…For example, enhanced expression and increased activity of two PLD isoforms have been found in cancer cells and tissues (33)(34)(35). We have observed that ADP-ribosylation factoractivated PLD activity was transiently increased in regenerating liver nuclei and that PLD2 levels were markedly elevated in the nuclei of hepatoma and kidney tumor cells (35,36). There is also evidence that PLD2 levels are markedly elevated in the caveolae of stimulated oncogenic cells and multidrugresistant cancer cells (37,38).…”
Section: The Relationship Between Ews-fli1 and Pld Expression In Cellmentioning
confidence: 55%
“…For example, enhanced expression and increased activity of two PLD isoforms have been found in cancer cells and tissues (33)(34)(35). We have observed that ADP-ribosylation factoractivated PLD activity was transiently increased in regenerating liver nuclei and that PLD2 levels were markedly elevated in the nuclei of hepatoma and kidney tumor cells (35,36). There is also evidence that PLD2 levels are markedly elevated in the caveolae of stimulated oncogenic cells and multidrugresistant cancer cells (37,38).…”
Section: The Relationship Between Ews-fli1 and Pld Expression In Cellmentioning
confidence: 55%
“…The PM localization was reported to be consistent with high basal activity of the PLD2 isoform with no significant contribution from PLD1 (37). PLD1 was localized to the PM and intracellular vesicles in activated macrophages and PLD2 to the nucleus (59,60). Studies in rat embryo fibroblasts and COS-7 cells localized PLD1 to Golgi, endoplasmic reticulum, and secretory vesicles (56,58).…”
Section: Discussionmentioning
confidence: 99%
“…PLD1 was also found to be associated with caveolae-enriched microdomains (61). Therefore, there is no general consensus concerning the localization of PLD isoforms (59). Due to detection limits in assaying endogenous PA in the CV membrane, here we localize PLD activities by labeling CSC and CV with NBD-PC.…”
Section: Discussionmentioning
confidence: 99%
“…This response may be mediated in part via other members of the mitogenactivated protein kinase family, eg, p38 and JNK. 36 -39 Oleic acid can potently stimulate nuclear phospholipase D. However, the nuclear ADP-ribosylation factor-dependent phospholipase D activity is associated with cell proliferation, 40,41 while oleate-dependent phospholipase D activitity is not.…”
Section: Signaling Events In the Mitogenic Interaction Between Oleic mentioning
confidence: 99%